Total protein, albumin and electrophoretic pattern of follicular fluid of goat ( Capra hircus) - BORDOLOI, P K; SARMAH, B C; DUTTA, D J; DEKA, B C (The Indian Journal of Animal Reproduction, 2023)
To inves tigate various biochemical constituents in follicular fluid of small (2-3 mm), medium (>3-S mm) and large (>Smm in :li ameter) fo lli cles, goat ovaries were obtained from abbatoir immediately after slaughter. For analysis of total protein,albumin and electrophoretic pattern of different protein fractions, pooled follicular fluid from identical follicles (based on diameter)was used. Both total protein and albumin levels in follicular fluid demonstrated declining trend along with increase in follicular size.Electrophoresis of fo llicular fluid showed five bands in contrast to six bands control serum samples. The protein bands of y-globulinwas not vis ible in the fo llicul ar fluid.
Keywords: Total protein; albumin; electrophoretic pattern; follicular fluid; goat